PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR - Rini Kristiantari , Maria Goreti; Rini Kristiantari, Chindytia; Anindya, Ayu; Nita Cahyani, Ayu; Pranantha, Radea (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to analyze the use of instructional media in improving writing skills of elementary school students. Writing is an essential language skill; however, many students still experience difficulties in generating ideas, organizing texts, and applying proper language rules. Therefore, the use of appropriate instructional media is needed to support the learning process. This study employed a literature review method with a descriptive qualitative approach by analyzing relevant scientific articles published between 2020 and 2025. The data were collected through academic databases such as Google Scholar and Garuda, then analyzed using content analysis techniques to identify types of media, their implementation, and their impact on students’ writing skills. The results indicate that visual, audiovisual, concrete, and collaborative media significantly contribute to improving students’ writing skills, particularly in idea development, text organization, and learning motivation. The use of instructional media also creates a more engaging and meaningful learning environment. Thus, selecting appropriate and varied instructional media is an effective strategy to enhance elementary students’ writing skills. Keywords: writing skills, instructional media, elementary school